2021
DOI: 10.14569/ijacsa.2021.0120613
|View full text |Cite
|
Sign up to set email alerts
|

A Review on SDR, Spectrum Sensing, and CR-based IoT in Cognitive Radio Networks

Abstract: The inherent scarcity of frequency spectrum, along with the fixed spectrum allocation adopted policy, has led to a dire shortage of this indispensable resource. Furthermore, with the tremendous growth of wireless applications, this problem is intensified as the unlicensed frequency spectrum becomes overcrowded and unable to meet the requirement of emerging radio devices operating at higher data rates. Additionally, the already assigned spectrum is underutilized. That has prompted researchers to look for a way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Thanks to technological developments, this idea has evolved over time, and the solution has now been commercialised. An interesting review on SDR in function of spectrum sensor can be found in [13].…”
Section: Sdr Fundamentalsmentioning
confidence: 99%
“…Thanks to technological developments, this idea has evolved over time, and the solution has now been commercialised. An interesting review on SDR in function of spectrum sensor can be found in [13].…”
Section: Sdr Fundamentalsmentioning
confidence: 99%
“…Radio technology is required as a cognitive network in order to overcome the problems in the unused spectrums. [35] The research that is being done in this field is still in its early phases, but it is progressing very quickly(M. Awasthi, 2017) [11]. The military, health care, household appliances, real-time monitoring, and vehicle networks are some of the prospective industries that could benefit from CR (Muhammad Hamad Alizai, 2009) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Through IoT, things will communicate with each other and develop their own intelligence. Smart-phones, cars, TVs, kitchen appliances, utility meters, thermostats, surveillance cameras, cardiac monitors, and almost everything, we can imagine will be connected every day, everywhere, and everytime [6]. The application of IoT technology will be present in all sectors and industries, from the smart home to the smart city, education, healthcare, manufacturing, energy, utilities, commerce, transportation, surveillance, supply chain, and logistics [7]- [9].…”
Section: Introductionmentioning
confidence: 99%